Lifetime Medical Costs of Genital Herpes in the United States: Estimates From Insurance Claims. Issue 4 (April 2021) - Eppink, Samuel T.; Kumar, Sagar; Miele, Kathryn; Chesson, Harrell W.
Abstract : Background: The purpose of this study was to estimate the lifetime direct medical costs per incident case of genital herpes in the United States. Methods: We used medical claims data to construct a cohort of people continuously enrolled in insurance for at least 48 consecutive months between 2010 and 2018. From this cohort, we identified initial genital herpes diagnoses as well as the cost of related clinical visits and medication during the 36 months after an initial diagnosis. Lifetime costs beyond 36 months were estimated based on treatment use patterns observed in the 36 months of follow-up. Results: The present value of lifetime direct medical costs of genital herpes was estimated to be $972 per treated case or $165 per infection (2019 dollars), not including costs associated with prevention or treatment of neonatal herpes. The clinical visit at which genital herpes was first diagnosed accounted for 27% of lifetime costs. Subsequent clinical visits and medications related to genital herpes accounted for an additional 13% and 60% of lifetime costs, respectively. Conclusions: The results from this study can inform cost-effectiveness analysis of genital herpes control interventions as well as help quantify the cost burden of sexually transmitted infections in the United States. Abstract : Based on medical claims data, the average lifetime direct medical costs of genital herpes were estimated to be $972 (per treated case) and $165 (per infection) in 2019 dollars.